Youth and ICTs: The power of information - Hagen, Erica; Maron, Mikel (Technical Centre for Agricultural and Rural Cooperation, 2012)
The Map Kibera project works with young people from one of Africa's biggest slums. They use GIS, SMS, video and the web to gather data and make it available to the community, where it can be applied to influence policies related to the area